2017
DOI: 10.3390/pharmacy5030043
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pharmacy Practice in European Countries—The Polish Perspective

Abstract: Polish pharmacy practice and the distribution of medicinal products in some European countries are still going through a significant transformation. Changes postulated by the pharmacists should strengthen their role, and the place of community pharmacies in the health care system in the context of—among others—the introduction and popularization of pharmaceutical care. Subsequently, these efforts may essentially ensure the professional independence of the pharmacists. The introduction of pharmaceutical care to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
15
0
3
Order By: Relevance
“…This might be an effect of price competition among pharmacies and from the observation that the biggest chains located in urban areas might be more business-focused [1]. It could also result, as pointed out byŚwieczkowski et al [4], from the role of Polish pharmacists, who are limited in dispensing medicines. Nevertheless, the German example showed that patient-oriented services have been rather successful, owing to pharmacists' activities and not from any law amendments or the market deregulation implemented in Germany [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might be an effect of price competition among pharmacies and from the observation that the biggest chains located in urban areas might be more business-focused [1]. It could also result, as pointed out byŚwieczkowski et al [4], from the role of Polish pharmacists, who are limited in dispensing medicines. Nevertheless, the German example showed that patient-oriented services have been rather successful, owing to pharmacists' activities and not from any law amendments or the market deregulation implemented in Germany [9].…”
Section: Discussionmentioning
confidence: 99%
“…Employees working in less profitable pharmacies could be afraid of restructuring, especially in urban areas. This may be mainly related to the fact that under the geographic and demographic restrictions a new pharmacy cannot be opened to replace a closed-down one [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the second analysed phrase -"dyrektywa fałszywkowa" (ang. Falsified Medicine Directives) the values were λ1 = 6,33 [6,58] and λ2 = 3,15 [3,25], respectively. In both cases the difference was statistically significant with p < 0,001.…”
Section: Wstępmentioning
confidence: 99%
“…gdzie opieka farmaceutyczna i farmaceutyczne usługi kognitywne są na etapie projektowania i wstępnej implementacji, stanowi najbardziej fundamentalny obszar jej działalności [3]. Apteka definiowana jest również jako placówka ochrony zdrowia publicznego i z definicji powinna skupiać się nie tylko na potrzebach indywidualnego pacjenta, ale odrywać rolę w profilaktyce chorób i odpowiadać na potrzeby populacyjne [4].…”
unclassified